How can African agriculture adapt to climate change: Impacts of considering climate variability on investment decisions in Ethiopia - Block, Paul J.; Strzepek, Kenneth M.; Rosegrant, Mark W.; Diao, Xinshen (International Food Policy Research Institute, 2008)
Numerous studies indicate that agricultural production is sensitive to climate variability, and lack of infrastructure in developing countries increases vulnerability to extreme climate events. In Ethiopia, the historical climate record indicates frequent droughts and floods, which can devastate agricultural production and existing infrastructure. Too much precipitation can flood crops, rot or suffocate roots, and wash out roads, creating similar economic conditions to those resulting from drought. With 85 percent of the population living in rural areas, and most people depending on rainfed agriculture, Ethiopia’s social and economic welfare depends heavily on climatic conditions. This brief is based on a paper that uses an economywide, multi-sector, and multi-regional model to assess the impact of climate variability on the outcomes of prospective investment strategies for Ethiopia, as well as on the country’s gross domestic product growth rates and poverty rates.